Principles of Rock Bolting Design: Analysis with Reference to Natural Pressure Arch: Standards and Analysis for Underground Rock Bolting Design (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This article presents the standards of underground rockbolting structure. The things examined incorporate underground stacking conditions, characteristic weight zone around an underground opening, plan strategies, choice of rockbolt types, assurance of bolt length and dispersing, factor of security, and similarity between help components.